Detection of the corner points from a map / Siti Sarah Raseli ... [et al.] - Raseli, Siti Sarah; Mahat, Norpah; Afina, Amirhussain (Universiti Teknologi MARA, Kedah, 2021)
The important points in the image that can view the information and features of the image are known as the corner points. The corner points can be detected by using several techniques. The techniques that involve in the detection of corner points are known as corner detector. In this study, a new technique named FAST Corner Detector is proposed to detect the corner points of Kampung Bukit Kapar map. Detection of corner points accurately is significant to the image processing, which can reduce the noise and much of the calculations. In this study, the initial technique is smoothing the image and extracting the outline of the image. Then, FAST Corner Detector is used to detect the corner points by considering the amount of corner point detection and run time processing.